Judicial costs in commercial cases and their role in limiting recourse to the judiciary - Al- Ghuwairi, Saad Mutlaq Eid (Journal of Economic, Administrative and Legal Sciences, 2022)
In this research, the researcher discussed the court costs issue in the new court cost system issued in the Kingdom of Saudi Arabia in 2021, and how this system has affected and will affect the reduction of merchants and companies' recourse to the commercial court, as the court cost is a new issue in Saudi Arabia and has not been adequately analyzed so far.The researcher used the inductive- deductive method to track and analyze texts to reach the results. In this new system, the regulator wanted to reduce the vexatious litigations that hinder the judicial work within the courts and delay the adjudication of cases and the issuance of judgments in them, which is incompatible with the speed and credit upon which business is based, as well as to encourage individuals to document contracts and financial and commercial transactions.The researcher reached a set of results, including that the court cost system makes pleading before the court more serious by imposing court fees for litigation, and also contributes to reducing the number of vexatious litigations in the commercial field, which leads to improved judgments.The researcher made some recommendations, including the system's need for further improvements to achieve its objectives without compromising the right of individuals and companies to defend their rights and without questioning the free litigation and the right to litigation stipulated in the Basic Law of the Governance.
Keywords: judicial costs; free trial; commercial courts; litigation fees